Modeling Site Suitability and Capacity for Small Hydropower Generation in Edo State, Southern Nigeria - Fakpor, Akpofure Miller; Fagunloye, Olamiposi Caleb; Igben, Titus Endurance; Dada, Emmanuel (European Scientific Journal, ESJ, 2025)
The study evaluates the suitability of sites for small hydropower (SHP) development in Edo State, Nigeria, as a renewable energy source. The assessment integrates Geographic Information System (GIS) techniques with hydrogeological and remote sensing data, including precipitation, stream order, geology, slope, land use/land cover, and soil texture. A Multi-Criteria Decision Making (MCDM) approach, specifically the Analytical Hierarchy Process (AHP), was used to rank potential SHP sites based on their suitability for hydropower generation. The analysis identified three highly suitable locations for SHP development. The estimated gross annual energy outputs for these sites were 5.8 MW, 5.65 MW, and 6.1 MW, respectively. These findings indicate significant potential for SHP as a sustainable energy solution in the region. However, further considerations-such as the specific hydropower yield, the river course location, environmental sustainability, socio-cultural factors, and compliance with government policies-are crucial for successful development. The study underscores the importance of SHP in enhancing electrification efforts while promoting environmentally friendly and sustainable energy generation.